2018
DOI: 10.25182/jgp.2018.13.3.131-136
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference and Waist-to-Height Ratio as Indicators for Excess Adiposity in Adolescents

Abstract: The aimed of study was to evaluate the accuracy of Waist Circumference (WC) and Waist-to-Height Ratio (WHtR) for identification of excess adiposity in adolescents. The study design was diagnostic study. The subjects consisted of 620 adolescents (283 boys and 337 girls) aged 14-18 years. The classification of excess adiposity termed as overfat and obese was based on age-and sex-specific percent body fat cutoff values of body fat reference curves for children from the Growth Foundation. Receiver-operating charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Whereas research on students in 8 ASEAN countries found that 11.9% of female students had high WHtR (30). Other research conducted on students of SMAN 2 Ungaran, aged 14-18 years, showed a higher prevalence among female students than men (31). The high prevalence of WHtR in adolescents in Indonesia shows that anthropometric measurements of WHtR can already be done for early adolescents.…”
Section: The Correlation Between Whtr With Metabolic Syndromementioning
confidence: 94%
See 2 more Smart Citations
“…Whereas research on students in 8 ASEAN countries found that 11.9% of female students had high WHtR (30). Other research conducted on students of SMAN 2 Ungaran, aged 14-18 years, showed a higher prevalence among female students than men (31). The high prevalence of WHtR in adolescents in Indonesia shows that anthropometric measurements of WHtR can already be done for early adolescents.…”
Section: The Correlation Between Whtr With Metabolic Syndromementioning
confidence: 94%
“…Adolescents are still undergoing growth process so WHtR can give an overview about cardiovascular disease. Most scientists recommend WHtR in over nutrition screening for adolescents which can also function as a risk predictor of noncommunicable diseases such as cardiovascular disease, because WHtR can describe body fat percentage and adipose tissue/visceral fat mass (31,32). Some studies also reported that WHtR is a better indicator than Body Mass Index (BMI) and waist circumference to identify obesity, because it affects changes in height, age and gender differences (13,33).…”
Section: The Correlation Between Whtr With Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Namun, nilai rata-rata pada penelitian ini lebih tinggi daripada nilai pada penelitian sebelumnya dengan rata-rata 69,08 cm. 24 Sampel yang memiliki lingkar pinggang tinggi ≥80 cm, ditemukan hanya sebesar 24,1 persen pada kelompok Fe dan 40,7 persen pada kelompok Fe+Vit C. Sedangkan berdasarkan IMT/U, sampel dengan IMT/U yang dikategorikan tinggi yaitu overweight dan obesitas ditemukan pada kelompok Fe+Vit C hanya sebesar 7,4 persen dan 3,7 persen dan pada kelompok Fe sebanyak 10,3 persen dan 3,4 persen. Lingkar pinggang dapat mewakili indikator obesitas sentral yang dapat memprediksi keberadaan lemak abdominal (distribusi lemak) yang erat kaitannya dengan perkembangan penyakit kardiovaskuler, sebaliknya IMT digunakan sebagai indikator adiposa secara keseluruhan yang menggambarkan status gizi secara umum.…”
Section: Pembahasanunclassified
“…Obesity could be interpreted by using anthropometric measurement such as Body Mass Index (BMI) and Waist Circumference (WC), which are used as one of the predictor for metabolic syndrome (Wong et al 2021). Similarly, increasing waist circumference (Ross et al 2020) and Waist to Hip Circumference Ratio (WHR) could represent abdominal adiposity when compared to BMI (Mulyasari & Pontang 2018). Previous study also found that WC and WHR can be used for predicting insulin resistance in adolescents (Fitriyanti et al 2019).…”
Section: Introductionmentioning
confidence: 99%